Perbaikan Desain Antarmuka Sistem Pelaporan Kehilangan Menggunakan Metode Human Centered Design (HCD) (Studi Kasus: SPKT Polres Tulungagung) - Grenzya Laksmi Putri Kusoy; Hanifah Muslimah Az-zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Sentra Pelayanan Kepolisian Terpadu (SPKT) is a police unit in charge of providing services to the public in the form of acceptance and first handling of reports/complaints, assistance services/police officers in accordance with the provisions of applicable laws and regulations. Lost Reporting Application can facilitate the Integrated Police Service Center of Tulungagung in creating reports for public reporting and can analyze the types of reports that have been reported in realtime. Lost Reporting Application owned by Tulungagung Integrated Police Service Center, the appearance was improved using the Human-Centered Design (HCD) method, with the interview techniques that resulted in PACT analysis and persona, further tested with usability testing, and the results of improvements in the form of prototypes. Prototype and testing design have been running according to user context and user needs. In initial testing, the results of two respondents failed to work on two assignments, and the average respondent worked nine tasks by 10 minutes to 13 minutes. Final usability testing gets the average result of nine tasks by 9 minutes to 13 minutes without any failure of respondents to perform the task after design improvements. So this research has been done and can solve problems in reporting applications lose using the method of Human-Centered Design (HCD).